Real-life evaluation of incidence and clinical outcomes of COVID-19 among healthcare workers during pre-vaccination and post-vaccination periods: A cross-sectional impact study - Ozdemir, Yusuf Emre; Sezen, Aysegul Inci; Surme, Serkan; Senoglu, Sevtap; Yesilbag, Zuhal; Sahin Ozdemir, Meryem; Bayramlar, Osman Faruk; Duman, Emine Ilay; Bold, Nomin; Gedik, Habip; Kart Yasar, Kadriye (The Journal of Infection in Developing Countries, 2023)
Introduction: We aimed to evaluate the prevalence and clinical outcomes of COVID-19 in healthcare workers (HCWs) in the pre-vaccination and post-vaccination periods. In addition, we determined factors associated with the development of COVID-19 after vaccination. Methodology: In this analytical cross-sectional epidemiological study, HCWs who were vaccinated between January 14, 2021, and March 21, 2021, were included. HCWs were followed up for 105 days after the 2 doses of CoronaVac. Pre-vaccination and post-vaccination periods were compared. Results: A total of 1,000 HCWs were included, 576 patients (57.6%) were male, and the mean age was 33.2 ± 9.6 years. In the last 3 months during the pre-vaccination period, 187 patients had COVID-19, and the cumulative incidence of COVID-19 was 18.7%. Six of these patients were hospitalized. Severe disease was observed in three patients. In the first 3 months post-vaccination period, COVID-19 was detected in 50 patients, and the cumulative incidence of the disease was determined to be 6.1%. Hospitalization and severe disease were not detected. Age (p = 0.29), sex (OR = 1.5, p = 0.16), smoking (OR = 1.29, p = 0.43), and underlying diseases (OR = 1.6, p = 0.26) were not associated with post-vaccination COVID-19. A history of COVID-19 significantly reduced the likelihood of the development of post-vaccination COVID-19 in multivariate analysis (p = 0.002, OR = 0.16, 95% CI = 0.05-0.51). Conclusions: CoronaVac significantly reduces the risk of SARS-CoV-2 infection and alleviates the severity of COVID-19 in the early period. Additionally, HCWs who have been infected and vaccinated with CoronaVac are less likely to be reinfected with COVID-19.